Briefing Note: Proceedings of the Singapore National Clinical Pharmacy Colloquium-Health Manpower Development Planning - Richard H. Parrish; Lita Chew (MDPI AG, 2018)
The nation of Singapore highly values its health service as well as the component of healthcare delivery that includes clinical pharmacy and administration. The Ministry of Health (MOH) engaged the services of Dr. Richard Parrish to better understand the relationship between the Singaporean citizenry and its clinical pharmacists. Through a series of five lectures, structured from the national to local unit level, four roundtables, two hands-on sessions, and three workshops, clinical pharmacists and administrative leadership participated in “open-mic” style lectures, discussed the issues facing Singapore pharmacy in its current provision of healthcare services, and deliberated on the future resources required to meet projected healthcare needs. From three distinct perspectives, these discussions were very frank, transparent, and passionate about what practitioners and administrators thought Singaporean health leadership needed to address in terms of (1) what programs and practices to continue; (2) what ones to start; and (3) what ones to evaluate. Each of the areas below will be framed using these three perspectives in order to clearly reflect the ideas and suggestions expressed in each of the 14 group sessions. These recommendations are forwarded to MOH pharmacy leadership for consideration and action. In addition, we met with MOH leaders regarding non-medical prescribing (NMP), and discussed strategies and tactics that seemed successful as well as unsuccessful in other jurisdictions when adopting expanded scope models for clinical pharmacists and other qualified healthcare providers that include prescribing of medications.